Inclined droplet train impingement on glass and aluminum substrates - Heng, Sheng Quan (Nanyang Technological University, 2021)
Single and droplet train impingement have been widely studied over the years due to its application in the industry. Current industrial application such as spray cooling requires the understanding of the hydrodynamic behaviours and heat transfer of droplet impingement. This field of study has not been well explored, where it lacks in-depth research and experiment of different parameters. Additionally, there are very few studies done on inclined flow droplet train impingement which could also affect the hydrodynamic behaviours and the cooling efficiency. Therefore, the objective of this project is to investigate on the effects of Weber number with an inclined flow on hydrodynamic behaviours and heat transfer of ethanol droplet train impingement onto a temperature gradient glass and aluminum substrates surfaces. Experiments were conducted with ethanol fluid on two types of surfaces, Glass and Aluminum which have different thermal conductivity. The Weber numbers of 617.67 and 791.51 are obtained with the diameter of nozzle generator of 100 and 150 microns. These Weber numbers are conducted on the Aluminum surface. Where the Weber numbers of 667.57, 841.90 and 998.00 were conducted on Glass surface. These Weber numbers of ethanol train droplet were conducted on these two types of surfaces of temperature gradient range of 80°C to 260°C. The hydrodynamic behaviours and thermal activity are being recorded using a high-speed camera and a thermal imaging camera. The results revealed that the spread length and splashing angle depends on the Weber number and surface temperature of each surface. The spread length trends on both surfaces are similar, it is observed that the spread length increase with increment in Weber numbers as well as decreases when surface temperature increases. The splashing angle were not prominent in glass as compared to aluminum surface. This is mainly due to the evaporation rate of the surface is not higher than the supply rate of ethanol liquid causing liquid pool accumulation. With the observation of splashing angle and spread length, transition regime can be identified. Transition regime occurs at different range of temperatures between different Weber number. It occurs at a lower temperature range of 140°C to 185 °C at high Weber number and occurs in 170°C to 200°C in lower Weber number on aluminum surface. The high splashing angle and large secondary droplets indicate the Leidenfrost point, which results in lower energy absorption rate between the aluminum surface and the ethanol droplet. Even with the decrease in temperature intervals to 15°C, the precise temperature where the Leidenfrost effect occurs still could not be precisely identified. In the future studies, smaller temperature intervals should be considered for more precise temperature identification of the Leidenfrost point.